Measuring the effectiveness of organizational immune system functions: an analytical exploratory study in the Iraqi Airways Company - Alaa Farhan Talib; Bushra Mohammed Alwan (Iraqi Journal for Administrative Sciences, 2024)
The purpose of the research is to test the effectiveness of organizational immune system functions at the airline have been test functions (perception, immune defense, stability of immune, immune memory, control) conducted on the sample induced Board workers and Council members and department heads and internal oversight body and a number of experts and advisers, targeted research to verify the effective functioning of the system functions and expected the findings will have completed an analysis and diagnosis of the effectiveness of each function, used non parametric statistical analysis tools, came up with the conclusion of the immune system is Organizational more vulnerable uncertainty. And most agree with the strategy of human resources information systems adopted in the company and a recommendation to move the company to build early warning systems and sensors for the company as long as they are affected by environmental uncertainty. We must reconsider the attraction and polarization strategy adopted.